Figurative Language in “Mysterious Things” Segment of Hirotada Radifan’s YouTube Channel - Puspa Fortuna Zulfa; Imam Tazali (International Journal of English Learning and Applied Linguistics (IJELAL), 2022)
The existence of figurative language in every people’s communication indicates the uniqueness of language itself. It beautifies oral and written communication. This research aims to find out and describe the use of figurative language in ‘Mysterious Things’ segment of Hirotada Radifan’s YouTube channel. There were 28 videos has been collected from the YouTube channel using Simak and Catat method in 3 months. For analyzing the data, Pilah Unsur Penentu method was implemented. The result of this research was presented using sentence form and it showed that the figurative languages often used by the speaker were simile, sarcasm, metaphor, satire, hyperbole, and irony. Besides, the performative utterances found in this research were exercitives, behabitives, and expositives. In conclusion, the unique utterances in each of his video contains various figurative language to beautify the speech and entertain the viewers so it can increase the viewers and subscribers.